Observation of A-B Phase Transition of Superfluid 3He by Transverse Acoustic Response - Saitoh, M; Wada, Y; Aoki, Y; Nishida, R; Nomura, R; Okuda, Y (AIP Conference Proceedings, 2006)
By using an AC-cut quartz transducer at the frequencies of 9.56 and 28.7 MHz, we observed discontinuity in the temperature dependence of transverse acoustic impedance of superfluid 3He at 24.9 bar. Though the transverse acoustic response of superfluid 3He is not well understood, we can conclude that the discontinuity occurred at the A-B transition, from its temperature and frequency dependence. Since the density of states near the boundary within a coherence length dominates the momentum transfer between an oscillating wall and 3He quasi-particles, the large difference in the transverse acoustic impedance between the A and B phases can be explained by a difference in the symmetry of the order parameters near the wall.